Do the interpersonal effects of gamified online destination websites better stimulate tourists’ travel intentions? - Hengji Wang; Mingze Qu; Yang Liu; Wenbo Li (PLoS ONE, 2025)
With the growing prevalence of user-generated content in disseminating travel information, the current design of online destination websites should emphasize interactive engagement and fulfill users’ increasing social needs, thereby aligning with the behavioral characteristics and development trends of the digital age. This study conducts two empirical studies to examine the feasibility of integrating gamification into destination platforms and its influence on interpersonal value within users’ decision-making processes. Through scenario-based simulations comparing feedback from 931 participants on gamified versus non-gamified websites, the study applies structural equation modeling to test path coefficients and confirm the effectiveness and advantages of gamification, as well as the role of interpersonal value in shaping decision-making pathways. This study found that: (1) Gamification effectively brings personal hedonic and utilitarian value, is suitable for destination websites, and positively influences user decisions. (2) There is no significant difference between gamified and non-gamified experiences in terms of utilitarian and hedonic value experiences, nor in the influence of utilitarian value on decision-making. (3) The personal value experience brought by gamification will positively influence users’ interpersonal value. (4) Interpersonal value—experience sharing, identity recognition, and social support—under gamified experiences will positively influence user decisions. These findings reveal that gamified design can not only effectively enhance the practical attributes of online destination websites but also significantly strengthen individuals’ information dissemination about the destination and activate the website’s interpersonal effects. This makes gamification a new model for optimizing the information display of existing online destination websites, and it highlights the crucial role of interpersonal value in studying consumer decision-making paths.